2022
DOI: 10.3390/foods11030373
|View full text |Cite
|
Sign up to set email alerts
|

Oyster (Crassostrea gigas) Extract Attenuates Dextran Sulfate Sodium-Induced Acute Experimental Colitis by Improving Gut Microbiota and Short-Chain Fatty Acids Compositions in Mice

Abstract: Drugs for inflammatory bowel diseases can be associated with serious side effects, and the development of alternative candidate resources derived from natural products has attracted considerable attention. Oyster extract (OE) derived from Crassostrea gigas contains glycogen, taurine, and amino acids, and has been assigned diverse health-promoting properties. This study investigated the anti-colitis effect of OE intake on fecal microbiota and its metabolites of acute experimental colitis mouse model induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
(63 reference statements)
3
9
0
Order By: Relevance
“…Compared with the control + DSS group, OE intake (the OE + DSS group) could alleviate colonic length shortening, as well as increase in the relative spleen weight, colonic histopathological scores (regeneration), and blood in the stool scores on day 16 (a DAI evaluation item). Previously, we reported that OE intake has an ameliorative effect on acute experimental colitis induced by DSS administration [ 15 ]. These indicate that OE intake ameliorates acute and chronic experimental colitis induced by DSS administration.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Compared with the control + DSS group, OE intake (the OE + DSS group) could alleviate colonic length shortening, as well as increase in the relative spleen weight, colonic histopathological scores (regeneration), and blood in the stool scores on day 16 (a DAI evaluation item). Previously, we reported that OE intake has an ameliorative effect on acute experimental colitis induced by DSS administration [ 15 ]. These indicate that OE intake ameliorates acute and chronic experimental colitis induced by DSS administration.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of OE from C. gigas , as well as its nutrient composition, have been described in our previous report [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations